Factors associated with prolonged length of stay in dengue hemorrhagic fever patients at Wangaya Hospital, Denpasar, Bali - Kunti, Desak Putu Sukasanti Adi; Suryana, Ketut (International Journal of Advances in Medicine, 2024)
Background: Dengue hemorrhagic fever (DHF) is a vector bone disease which is being a serious public health concern in tropical and sub-tropical countries around the world. A high number of dengue cases are reported annually in Bali. Prolonged hospital stays affect the high cost of dengue treatment. The aim of the study was to analyze the factors associated with prolonged lengths of stay in dengue hemorrhagic fever patients. Methods: This study was an analytic observational study with a retrospective study design. The data was collected from the medical records of DHF patients at Wangaya Hospital between January - May 2024. The data analysis method used was the Chi square test as a bivariate test. Results: A total of 152 subjects, mostly DHF patients, were male (54.61%), <40 years old (73.68%), without comorbid disease (71.05%), without low food intake (56.58%), and with a length of stay ≥4 days (66.45%). Most of the patients (>50%) had clinical symptoms of fever (100%), headache (91.45%), and myalgia (83.55%). A statistically significant association was found between comorbid disease and prolonged length of hospital stay with a p value of 0.039 (p<0.05), and low food intake showed a significant association with prolonged length of stay with a p value of 0.001 (p<0.05). Conclusions: This study identified that comorbid disease and low food intake were factors associated with prolonged lengths of stay in DHF patients. Findings of this study may still prove beneficial for physicians to do early identification of DHF patients who have high risk factors for prolonged hospitalization, which can be an effective tool to combat the increasing disease burden.